Clinical outcome of acute thoracic aortic syndrome in nonagenarians. (November 2020) - Arakawa, Mamoru; Okamura, Homare; Miyagawa, Atsushi; Kitada, Yuichiro; Adachi, Hideo
Background: Decision-making regarding the operability of thoracic aortic disease in nonagenarian patients remains controversial because outcomes of open surgical repair of the thoracic aorta are unclear. We investigated the surgical and nonsurgical outcomes of acute thoracic aortic syndrome treatment in nonagenarians. Methods: After evaluating data in our institute from April 2016 to March 2020, we included 10 nonagenarians who needed surgical intervention on the thoracic aorta via a median sternotomy for acute thoracic aortic syndrome. The mean age of the cohort was 91.9 ± 2.1 years. Five patients underwent open surgical repair of the thoracic aorta (surgical group), and 5 refused surgery (nonsurgical group). All patients in the surgical group performed activities of daily living independently, with a mean clinical frailty scale of 3.2 ± 0.4. The surgical group included 4 patients with type A aortic dissection and one with a ruptured thoracic aortic aneurysm. Hemiarch replacement was performed in 3 patients and total arch replacement in 2. The mean follow-up period was 17.8 ± 5.1 months. Results: Hospital mortality rates were 0% in the surgical and 80% in the nonsurgical group. The mean length of hospitalization was 28.4 ± 6.7 days in the surgical group. The 1-year survival rates were 100% in the surgical group and 20% in the nonsurgical group. Conclusion: Open surgical repair for acute thoracic aortic syndrome via median sternotomy is a reasonable treatment option even in nonagenarians. Involvement of family members is important for decision-making to devise the optimal treatment strategy (surgical vs. medical).